Pengaruh Perbandingan Konsentrasi Asam Sitrat-Malat terhadap Karakteristik Granul Effervescent Daun Katuk (Sauropus androgynus L. Merr) - Cahya Ningrum, Made Yuni; Diah Puspawati, Gusti Ayu Kadek; Ayu Ekawati, I Gusti (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
The purposes of this research was to determine the effect of concentration ratio of citric-malic acid on the characteristics of the effervescent granule of katuk leaves and to proper concentration ratio of citric-malic acid to get the effervescent granule of katuk leaves with the best characteristics. The research used Completely Randomized Design (CRD) with the treatment of concentration ratio of citric-malic acid consisting of 5 levels: 5% : 25%, 10% : 20%, 15% : 15%, 20% : 10%, dan 25% : 5%. The treatment was repeated 3 times in order to obtain 15 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan's Multiple Range Test. The result showed that concentration ratio of citric-malic acid had a significant effect (P<0,05) on moisture content, ash content, flow time, soluble time, high foaming, total flavonoids, and antioxidant capacity. The concentration ratio of 5% citric acid and 25% malic acid was the best treatment to produce effervescent granule of katuk leaves with the moisture content 5.67%, ash content 23.84%, pH 5.88, soluble time 20.69 seconds, flow time 0.80 seconds, high foaming 3.20 cm, total flavonoids 21.04 mgQE/100g powder, antioxidant capacity 16.51 mgGAEAC/100g powder sensory hedonic of the color was liked, the aroma was liked, the taste was liked and the overall acceptance was liked.